Esophageal balloon tamponade versus esophageal stent in controlling acute refractory variceal bleeding: A multicenter randomized, controlled trial. Issue 6 (14th January 2016) - Escorsell, Àngels; Pavel, Oana; Cárdenas, Andrés; Morillas, Rosa; Llop, Elba; Villanueva, Càndid; Garcia‐Pagán, Juan C.; Bosch, Jaime; ,
Abstract : Balloon tamponade is recommended only as a "bridge" to definitive therapy in patients with cirrhosis and massive or refractory esophageal variceal bleeding (EVB), but is frequently associated with rebleeding and severe complications. Preliminary, noncontrolled data suggest that a self‐expandable, esophageal covered metal stent (SX‐ELLA Danis; Ella‐CS, Hradec Kralove, Czech Republic) may be an effective and safer alternative to balloon tamponade. We conducted a randomized, controlled trial aimed at comparing esophageal stent versus balloon tamponade in patients with cirrhosis and EVB refractory to medical and endoscopic treatment. Primary endpoint was success of therapy, defined as survival at day 15 with control of bleeding and without serious adverse events (SAEs). Twenty‐eight patients were randomized to Sengstaken‐Blakemore tube (n = 15) or SX‐ELLA Danis stent (n = 13). Patients were comparable in severity of liver failure, active bleeding at endoscopy, and initial therapy. Success of therapy was more frequent in the esophageal stent than in balloon tamponade group (66% vs. 20%; P = 0.025). Moreover, control of bleeding was higher (85% vs. 47%; P = 0.037) and transfusional requirements (2 vs 6 PRBC; P = 0.08) and SAEs lower (15% vs. 47%; P = 0.077) in the esophageal stent group. TIPS was used more frequently in the tamponade group (4 vs. 10; P = 0.12). There were no significant differences in 6‐week survival (54% vs. 40%; P = 0.46). Conclusion: Esophageal stents have greater efficacy with less SAEs than balloon tamponade in the control of EVB in treatment failures. Our findings favor the use of esophageal stents in patients with EVB uncontrolled with medical and endoscopic treatment. (Hepatology 2016;63:1957‐1967)